Histological, immunohistochemical and ultrastructural features of the fetal liver morphology under the influence of lead and nanometals. - Shatorna, V. F.; Belska, Yu. O.; Harets, V. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Silver and gold have a special place among the variety of minerals. However, the morphology liver at histological and ultramicroscopic level under the combined effect of lead acetate and silver and gold citrates have been insufficiently studied. Objective. Identifying of morphological changes in the liver of rats fetuses as a result of combined influence of lead citrate with silver and gold citrates. Methods. The rats were divided into four groups: control group - animals treated with distilled water; group Pb - animals treated with a solution of lead acetate at a dose of 0.05 mg / kg; group Pb + Ag - animals treated with a solution of lead acetate at a dose of 0.05 mg / kg and silver citrate at a dose of 2 mg / kg; group Pb + Au - animals treated with a solution of lead acetate at a dose of 0.05 mg / kg and gold citrate at a dose of 1.5 mg / kg. On the 20th day of pregnancy performed an autopsy, the liver of fetuses was removed and examined its morphological state. Results. In fetal liver of 20th day of embryogenesis identified increased intensity of accumulation of vimentin, accumulation of marker Ki67 was reduced in comparison to the control group. Degenerative changes in hepatocytes and nucleoli disintegration was identified on ultramicroscopic level. Moderate and uniform accumulation of vimentin in liver tissue of the fetuses was revealed in case of the combined injection of lead acetate and silver citrate. Accumulation of marker Ki67 was increased compared to group of lead exposure. Increase of the number of mitochondria and ribosomes was detected on ultramicroscopic level. Under the combined influence of lead acetate and gold citrate the extensive accumulation of vimentin and decreased level of marker Ki67 was identified. Conclusion. Silver citrate on the background of lead exposure showed compensatory properties, that manifested in decreasing of hepatotoxicity caused by lead acetate.